2015
DOI: 10.13181/mji.v24i4.1266
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated tuberculosis diagnosed first as leptospirosis in immunocompetent patient

Abstract: ABSTRAK

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Several studies have shown that the sensitivity of AFB and PCR on liver tissue is inconclusive; conversely, the sensitivity of liver biopsy to caseating granulomas is 91%–100%. [ 1 49 63 64 65 ]…”
Section: Focused Diagnostic Workupmentioning
confidence: 99%
“…Several studies have shown that the sensitivity of AFB and PCR on liver tissue is inconclusive; conversely, the sensitivity of liver biopsy to caseating granulomas is 91%–100%. [ 1 49 63 64 65 ]…”
Section: Focused Diagnostic Workupmentioning
confidence: 99%